An unusual cause of gastrointestinal bleeding and intestinal obstruction - Rosario Arena; Stefano Gasperoni; Andrea Lisotti; Chiara A. A. Petrini; Mario L. Brancaccio; Omero Triossi; Alessandro Mussetto (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Arena R, Gasperoni S, Lisotti A, et al. An unusual cause of gastrointestinal bleeding and intestinal obstruction. Turk J Gastroenterol 2018; 29: 365-6.